Cercaria of the Trematode Plagiorchis mutations (Trematoda, Plagiorchiidae) from the Ponds Snails, Lymnaea stagnalis, in Ukraine - Zhytova, O.P. (Вестник зоологии, 2010)
Morphological characteristics and measurements of Plagiorchis mutationis Panova, 1927 cercaria found for the first time in the intermediate host, pond snail Lymnaea stagnalis in Ukraine are given. Дана морфологическая характеристика церкарий трематоды Plagiorchis mutationis Panova, 1927, впервые обнаруженной на территории Украины в промежуточном хозяине большом прудовике, Lymnaea stagnalis.